You need to have all terms to the left side.

Subtracting 3/2 both sides yields:

`(2x+3)/(x+2) - 3/2 = 0`

You need to bring both fractions to a common denominator such that:

`(2(2x+3) - 3(x+2))/(2(x+2)) = 0`

Opening the brackets yields:

`(4x + 6 - 3x - 6)/(2(x+2)) = 0`

`` `x/(2(x+2)) = 0`

The denominator of the fraction must not be zero => `x+2 != 0` => `x != -2` .

If the fraction yields 0 => x = 0.

**The solution to the given equation is x = 0.**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.